Manufacturing process development for engine construction parts from composite materials by 3D printing - Firsin, A O; Vdovin, R A; Goncharov, E S; Markanov, I D (Journal of physics. Conference series, 2024)
This paper represents the development of the general design algorithm for structures of parts made of composite materials in respect of the additive manufacturing technology. Information on the 3D printing technology by extrusion is provided. Main design stages for production tooling for the “Insert” part, with regard of possibilities and limitations of printing on 3D printers, are described. Roughness analysis of samples, manufactured on the 3D printer from various composite materials, has been carried out.